PENATAAN TAMAN KARTINI SEBAGAI HUTAN KOTA DI KOTA CIMAHI - Kusumawati, Ika; Hindersah, Hilwati (Jurnal Perencanaan Wilayah dan Kota, 2010)
Cimahi has been known since the Dutch colonial period, in 1811, when the Governor-General Willem Daendeles made road from Anyer to Panarukan and right in Cimahi square now was made Loji (Pos Penjagaan). The analysis process which is conducted in this research include population analiysis, analysis of green open space and urban forest structure. Population is used to determine the amount of population and its density distribution in the coming years.The need for green open space is used to determine the ideal area of urban forest and the amount of oxygen requirements for residents.While the structure of the urban forest is used in managing the urban forest vegetation.The final results achieved in this research is an arrangement concept of the urban forest in the Kartini Park. The concept is supported by the fact of: (1) the exterior arrangement which closely related to the maintenance of park and activities of visitors to the park, (2) Taman Kartini is surrounded by functional buildings, (3) Taman Kartini is located on three roads, namely Jalan Baros, Jalan Dustira/ Hospitaalweg, and Jalan Taman Kartini), and (4) planting vegetation criteria in accordance withTaman Kartini neighborhood.